2010
DOI: 10.1086/653665
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Exploiter‐Victim Coevolution: The Race Is Not Always to the Swift

Abstract: The modeling of coevolutionary races has traditionally been dominated by methods invoking a timescale separation between ecological and evolutionary dynamics, the latter assumed to be much slower than the former. Yet it is becoming increasingly clear that in many cases the two processes occur on similar timescales and that such "rapid" evolution can have profound implications for the dynamics of communities and ecosystems. After briefly reviewing the timescale separations most common in coevolution theory, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Our findings echo recent developments in evolutionary theory showing that complexity, defined as phenotype dimensionality234142 or overlapping ecological and evolutionary timescales43, can affect the evolutionary stability of a species and promote evolutionary diversification. A general picture is thus emerging: evolutionary diversification is more likely in complex ecological ecosystems, and the conditions permitting adaptive radiation could be much broader than previously thought.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings echo recent developments in evolutionary theory showing that complexity, defined as phenotype dimensionality234142 or overlapping ecological and evolutionary timescales43, can affect the evolutionary stability of a species and promote evolutionary diversification. A general picture is thus emerging: evolutionary diversification is more likely in complex ecological ecosystems, and the conditions permitting adaptive radiation could be much broader than previously thought.…”
Section: Discussionsupporting
confidence: 88%
“…The model encompasses most particular models of adaptive radiation that have been studied so far, and does not assume particular functional forms, allowing us to derive general insights4345. The abundance n i of a particular species i changes through time according to…”
Section: Methodsmentioning
confidence: 99%
“…In addition to accumulating empirical evidence of coevolution [1,5], recent studies have shown that evolution can be rapid enough to affect contemporary population dynamics [6][7][8]. Understanding 'rapid coevolution' is therefore important for understanding and predicting future ecological dynamics [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The second trait, s, determines the interaction between the herbivore and plant species (figure 1b). We use a Gaussiantype function of trait matching [31,32] and combine it with the herbivore thermal niche to form the grazing rate [33]:…”
Section: Materials and Methods (A) Modelmentioning
confidence: 99%